Seasonal Variation in Carcass Characteristics of Korean Cattle Steers - Piao, M. Y.; Baik, M. (Animal bioscience, 2015)
Climate temperature affects animal production. This study was conducted to evaluate whether climatic conditions affect beef carcass characteristics of Korean cattle steers. The monthly carcass characteristics of Korean cattle steers (n = 2,182,415) for 8 yr (2006 through 2013) were collected from the Korean Institute for Animal Products Quality Evaluation. Daily climate temperature (CT) and relative humidity (RH) data were collected from the Korean Meteorological Administration. Weather conditions in South Korea during summer were hot and humid, with a maximum temperature of 28.4°C and a maximum RH of 91.4%. The temperature-humidity index (THI), calculated based on CT and RH, ranges from 73 to 80 during summer. Winter in South Korea was cold, with a minimum temperature of -4.0°C and a wind-chill temperature of -6.2°C. Both marbling score (MS) and quality grade (QG) of Korean cattle steer carcasses were generally best (p<0.05) in autumn and worst in spring. A correlation analysis showed that MS and QG frequencies were not associated (p>0.05) with CT. Yield grade (YG) of Korean cattle steer carcasses was lowest (p<0.05) in winter (November to January) and highest in spring and summer (May to September). A correlation analysis revealed that YG frequency was strongly correlated (r≥0.71; p<0.01) with CT and THI values. The rib eye area, a positive YG parameter, was not associated with CT. Backfat thickness (BT), a negative YG factor, was highest in winter (November and December). The BT was strongly negatively correlated (r≤-0.74; p<0.01) with CTs. Therefore, the poor YG during winter is likely due in part to the high BT. In conclusion, YG in Korean cattle steer carcasses was worst in winter. QGs were not associated with winter or summer climatic conditions.